Anti-allodynic and antihyperalgesic activities of zerumbone in chronic constriction injury-induced neuropathic pain and its possible mechanism of action - Zulazmi, Nurul Atiqah (2016)
The present study was conducted to investigate the potential of zerumbone, a bioactive sesquiterpene of Zingiber zerumbet (L) Smith (Z. zerumbet) in anti-allodynic and antihyperalgesic properties in neuropathic pain induced by chronic constriction injury (CCI) in mice. We used this model and demonstrated the comparison of different number of sciatic nerve ligation (1, 2, 3 and 4). The outcome revealed that a single ligation CCI animal model on the sciatic nerve is enough to mimic the symptoms of neuropathic pain such as hyperalgesia and allodynia with almost similar effect with the usual 4 ligations sciatic nerve in CCI animal model. Indeed, acute and repeated intraperitoneal (i.p) administration (on 14th day and continued administration once daily for 7 days) of zerumbone (10, 50, 100 mg/kg) significantly exhibited dose-dependent inhibition of chronic constriction injury induced-neuropathic pain in mice, when evaluated using von Frey filament test, cold plate, Randall-Selitto and Hargreaves plantar test (p<0.05). The compound was found to exert anti-allodynic and antihyperalgesic properties in chronic constriction injury (CCI) model and the optimum dose for zerumbone was found out to be 10 mg/kg. The anti-allodynic and antihyperalgesic effect of zerumbone (10 mg/kg i.p) were also significantly reversed by pre-treatment of L-arginine (10 mg/kg), 1H [1,2,4] Oxadiazole [4,3a] quinoxalin-1-one (ODQ), soluble guanosyl cyclase blocker (2 mg/kg i.p) and glibenclamide (ATPsensitive potassium channel blocker) (10 mg/kg i.p). In addition, the histology of nerve morphology also showed a profound attenuation of mast cells around nerve fibres after treated 7 days daily with 10 mg/kg i.p and 50 mg/kg i.p of zerumbone (p<0.05). Even though, zerumbone failed to produce significant result with vehicle-treated group on the swelling of nerve fibre but the anti-inflammatory effect of zerumbone was able to attenuate the inflammatory cells surrounding the nerve fibre. Together, these findings proved that zerumbone produce pronounced anti-allodynic and antihyperalgesic effects in modified CCI model of neuropathic pain in mice that involves inhibition of Larginine- NO-Cyclic GMP (cGMP) pathway followed by the opening of ATP-sensitive K+ channel at the peripheral level. Hence, considering that few effective drugs that are available in the market for the treatment of neuropathic pain, this study indicates that zerumbone a potentially interesting in the development of new clinically relevant drugs for the management of chronic pain.